EANO-ESMO Clinical Practice Guidelines for diagnosis, treatment and follow-up of patients with leptomeningeal metastasis from solid tumours - Le Rhun, Emilie; Wick, Wolfgang (Annals of oncology, 2017)
© The Author 2017. Published by Oxford University Press on behalf of the European Society for Medical Oncology. All rights reserved. For Permissions, please email: journals.permissionsoup.com.These EANO-ESMO joint recommendations for the diagnosis and treatment of leptomeningeal metastasis (LM) from solid cancers represent the first European guideline initiative on this topic. LM is defined as the spread of tumour cells within the leptomeninges and the subarachnoid space, is synonymous with ‘neoplastic meningitis’ and can be further denoted by primary tumour as leptomeningeal carcinomatosis, gliomatosis or lymphomatosis. The recommendations address LM from solid tumours, but neither LM from primary brain tumours nor LM from lymphoma or leukaemia. They cover prevention, diagnosis, therapy and follow-up, but not differential diagnosis, adverse effects of therapeutic measures or supportive or palliative care. We propose diagnostic criteria as well as a neuroimaging- and cytopathology-based classification of LM syndromes to derive pragmatic treatment algorithms. We also assign...
Gesehen am 11.04.2018